1997
DOI: 10.1002/(sici)1099-1018(199701)21:1<23::aid-fam591>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐retardant Additives for Polymeric Materials—I. Char Formation from Silica Gel–Potassium Carbonate

Abstract: Silica gel combined with potassium carbonate is an effective fire retardant for a wide variety of common polymers (at mass fraction of only 10% total additive) such as polypropylene, nylon, polymethylmethacrylate, poly(vinyl alcohol), cellulose, and to a lesser extent polystyrene and styrene-acrylonitrile. The peak heat release rate is reduced by up to 68% without significantly increasing the smoke or carbon monoxide levels during the combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The value of HRRmax recorded for silicone rubber amounts to 115 kW m -2 , while the value of this parameter for organic polymer, determined for a heat flux equal to 35 kW m -2 , amounts to: for polypropylene 1800 kW m -2 [14], for PET 1600 kW m -2 [15], for low density polyethylene 1400 kW m -2 [16], and for NBR rubber 1100 kW m -2 [17].…”
Section: Flammability Of Silicone Rubber Compositesmentioning
confidence: 94%
“…The value of HRRmax recorded for silicone rubber amounts to 115 kW m -2 , while the value of this parameter for organic polymer, determined for a heat flux equal to 35 kW m -2 , amounts to: for polypropylene 1800 kW m -2 [14], for PET 1600 kW m -2 [15], for low density polyethylene 1400 kW m -2 [16], and for NBR rubber 1100 kW m -2 [17].…”
Section: Flammability Of Silicone Rubber Compositesmentioning
confidence: 94%
“…Among inorganic fillers added to PMMA, silica was the most widely investigated. [10][11][12][13][14] The thermal degradation of such composites was a prime areas of investigation. It was shown that the addition of silica into PMMA improves thermal stability of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…In premixed flames, Fe(CO) 5 and at low concentrations, reduced the burning velocities up to 100 times more effectively than CF 3 Br and showed a strong dependence on both the fuel-air equivalence ratio and oxygen mole fraction. However, at high concentration of Fe(CO) 5 there was no additional reduction of the burning velocity. In diffusion flames, Fe(CO)5 was again shown to be more effective at the lowest concentrations, but the inhibition effect did not level off at higher mole fractions as it did in premixed flames.…”
Section: Introductionmentioning
confidence: 97%
“…Further work was carried out to find alternative inhibitors. Gilman et al 5 found that the flammability limits of a wide variety of polymers were dramatically reduced in the presence of relatively small concentrations of silica gel and potassium carbonate (K 2 CO 3 ). The heat peak rate was reduced by 68% without significantly increasing the smoke or carbon monoxide levels during the combustion.…”
Section: Introductionmentioning
confidence: 99%